Letter (copy) : re Function - on 18/1/39 - B.M.A. House - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0052-001 Tele: Maida Vale 1384. 4, Aberdare Gardens, Hampstead, LONDON, N.W.6. 14th January, 1939. The Rt. Hon. Lord Addison, Coombe Cottage, Butler's Cross, ALYESBURY, Bucks. Dear Lord Addison, re Function - on 18/1/39 - B.M.A. House. I have spoken to Dr. Boyde, and have been trying to get into touch with you. It seems that the returned Medical members who were recruited through the Spanish Medical Aid Committee desire to appear at that function in evening dress. Boyde tells me that you are travelling down from the provinces just in time to turn up at this function. Will you be able to change into a dress suit? If not, then we will all go in plain clothes. If you can, then, it is agreed that the returned medical members and you and I will dress. This is not my idea but theirs. Everything depends on what you can do. With many thanks Yours sincerely, H.B.M. E.K. 292C/946/2/52